Efectos del calcio y sus reguladores hormonales y farmacológicos en el movimiento dental ortodóntico: una revisión sistemática (2022)
Orthodontic tooth movement (OTM) is a biological phenomenon that involves bone resorption and formation and in which calcium and its regulators play an essential role1 (Perez et al.,2020). The role of calcium in the human body can have effects on OMM, but these are not clear in the literature.